Repolarization dynamics stability in Brugada type-1 pattern subjects with positive and negative genetics - Sabatini, A; Pellegrini, N; Varriale, A; Piccolo, S; Capocci, S; Tomasi, L; Mugnai, G; Tomei, R; Franchi, E; Ribichini, F; Bolzan, B (Europace (London, England), 2024)
Abstract Background Brugada type-1 pattern (Brgd1) risk stratification in asymptomatic subjects and its repolarization dynamics are complex. Purpose This study aims to analyze, from alternative standpoints, superficial 12-lead ECG V1 repolarization patterns (repol.). This method diverges from standard ECG pattern characterization. It rather exploits nonlinear dynamics and stability of ECG repol. to assess stability driving cardiac dynamics. This work consists in analyzing 2 subjects with Brgd1: Subject1 with negative genetics and negative EP study. Subect2 with positive genetics. Target To deepen knowledge/insight and applications of control-and-stability-theory applied to 12-lead ECG, aiming to eventually diminish the number of invasive EP studies. Methods A stability control closed loop system has been designed to model electrophysiology dynamics of cardiac conduction: ECG segments being the input-output of the system. (Figure). A sequence of V1 repol. have been scanned, digitized, and quantitatively processed yielding stability parameters (poles in S-plane). Scanning and signal processing performed by Matlab R_2023b. Results Figures. Conclusions Based on our data, 12-lead-ECG repol. seem to be associated with increasing stability in Subject1, exhibiting negative genetics. On the other hand, less stability seems to be associated with Subject2, reporting positive genetic tests. In conclusion, furthering control-and-stability-theory applied to 12-lead ECGs aims to deeper comprehension of physiological and pathological substrates of malignant arrhythmias, and to focus on noninvasive risk stratification strategies for ICD implantation indication in BrS. Further development of this technique will be largely facilitated by the implementation of AI methodologies in the near future.